Viewing Cultural Barriers as Opportunities to Enhance Learning: An International Perspective - Rosemary S. Caffarella (Adult Education Research Conference, 2010)
I argue in this paper that although it is important to understand the key cultural barriers that can inhibit learning in international settings, it is also critical to think differently about these barriers as opportunities to enhance learning. Major cultural factors that influence the formation of these barriers, and examples of cultural barriers and strategies to turn these barriers into opportunities for positive action are discussed.